1992
DOI: 10.1002/ps.2780350310
|View full text |Cite
|
Sign up to set email alerts
|

Time, concentration and temperature relationships for phosphine activity in tests on diapausing larvae of Ephestia elutella (Hübner) (Lepidoptera: Pyralidae)

Abstract: The activity of phosphine against diapausing larvae of Ephestia elutella was shown to depend on several different interactions of duration of exposure, temperature and gas concentration. Using the model proposed by Knight, (C-C,) x ( t -to) = k , a constant for mortality, the minimum effective concentration C, was raised and the minimum effective exposure to extended as temperatures were increased. The effect of temperature on these thresholds was reduced at higher mortality levels. A range of concentration l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Statistical analysis indicated that C 0 was not significantly different from zero for all but two regressions (two formulations on the fungi). A minimal threshold value of zero ( C 0 ) was also obtained for methyl bromide and for different pests 25. A large b value indicates a steeper slope, ie a small change in concentration has a large effect on pest control.…”
Section: Resultsmentioning
confidence: 81%
“…Statistical analysis indicated that C 0 was not significantly different from zero for all but two regressions (two formulations on the fungi). A minimal threshold value of zero ( C 0 ) was also obtained for methyl bromide and for different pests 25. A large b value indicates a steeper slope, ie a small change in concentration has a large effect on pest control.…”
Section: Resultsmentioning
confidence: 81%
“…Model simulation using CTEI as a numeric variable can be used as an effective alternative to help make management decisions for soil fumigation by drip irrigation. The model prediction can be improved by inclusion of temperature effects on efficacy (Bell, 1992; Xue et al, 2000) in calculating CTEI. The modeling approach using CTEI is limited by the availability of threshold CT values for pest–pesticide combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Although useful, eqn (1) must be used with caution because the value of n may vary for a number of reasons. Within the same life stage the value of n may vary depending on fumigation temperature and the concentration range 2. Different values of n have been reported for adults of susceptible and resistant strains of the same species 3, 4.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of phosphine to grain insects has long been known to be influenced by both concentration and exposure period, and some researchers have sought to quantify these effects 1–6. In these published studies, insects were exposed to constant concentrations only.…”
Section: Introductionmentioning
confidence: 99%